Factors Predicting Leaving Against Medical Advice in Neurosurgery: A Prospective Observational Study - Ali Zain Ul Abidin, Hussnain Mohammad Buksh, Lt Col Ayyaz Hussain Awan Ti(M) (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The decision of a patient for leaving the hospital against medical advice (AMA)affects the patient management adversely by increasing morbidity, mortality and escalates the cost of treatment. Objectives: The main objective of the study is to find the factors predicting leaving against medical advice in neurosurgery. Material and methods: This cross-sectional study was conducted in King Edward Medical University during February 2022 to July 2022. Data was collected with the permission of ethical committee of hospital. Data on gender, age, marital status, day and time of admission and discharge, duration of stay, primary specialty for care, reason for leaving against medical advice, prior history of hospitalizations, mode of payment, medication and follow-up advice at time of LAMA, revisit to the hospital and development of morbidity at follow-up was collected from patient charts and the LAMA form. Results: Data was collected from 300 patients of both genders. There were 142 male and 158 female patients from age range 0 to 75 years. During the same period, 263 patients were discharged from the neurosurgical service and the rate of LAMA in the neurosurgery department was calculated to be 16.73%. Practical implication: This study will be helpful in neurology department of the hospital and used for the betterment of results. Conclusion: It is concluded that leaving AMA rates are high in neurological in-patients. Low income and level of health literacy were the most common causes of LAMA in this neurosurgical patient population. Keywords: LAMA, Patients, Surgical. Population, AMA, Health